2010
DOI: 10.1510/icvts.2010.243600
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury is decreased by late remote ischaemic preconditioning and aggravated by tramadol in patients undergoing cardiac surgery: a randomised controlled trial☆

Abstract: The purpose of this study was to test, whether the late phase of remote ischaemic preconditioning (L-RIPC) improves myocardial protection in coronary artery bypass grafting (CABG) with cold-crystalloid cardioplegia and whether preoperative tramadol modifies myocardial ischaemia-reperfusion injury using the same group of patients in a single-blinded randomized controlled study. One hundred and one adult patients were randomly assigned to either the L-RIPC, control or tramadol group. L-RIPC consisted of three fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 15 publications
3
54
0
Order By: Relevance
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysissupporting
confidence: 52%
See 3 more Smart Citations
“…Subgroup analysis of the studies reporting outcomes of CABG with or without AVR showed results consistent with the general trend (SMD -0.42; 95% CI: -0.70 to -0.13, p = 0.005) and I 2 = 67% [9,[20][21][22][23][24][25][26][27]. Studies concerning isolated valvular surgery did not confirm the protective result of rIPC; however, heterogeneity (I 2 = 94%) was essentially influencing the outcome effect under the random [28][29][30].…”
Section: Sensitivity Analysissupporting
confidence: 52%
“…Finally, fifteen papers were found to present the best available evidence. These studies pertained to: adult coronary bypass grafting surgery with or without AVR [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], adult valvular surgery [28][29][30], and pediatric cardiac surgery [31][32][33]. All the available papers were designed as prospective randomized controlled trials.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous similar adult study protocols, cuffs have been inflated to 200 or 40 mmHg above the patients' actual upper arm blood pressure [2,3]. Tourniquet pressures may cause complications such as soft tissue blisters, burns, rashes, abrasions, nerve-related injuries, and muscle injuries [4]. Lieberman et al [5] recommended that a cuff pressure of 50 mmHg above systolic blood pressure is sufficient to provide limb ischemia in pediatric patients.…”
mentioning
confidence: 99%